يوليوس قيصر وبوادر النظام الامبراطوري (102ق.م_ 44ق.م) - أمينة بن جمعة; د/صبيحة أوكيل (جامعة عمار ثليجي الاغواط, 2023)
الملخص تعتبرالحضارة الرومانية واحدة من اهم الحضارات في العالم القديم تمكنت من فرض سيطرتها على حوض البحر الابيض المتوسط خاصة بعد سقوط قرطاج انتقلت من مدينة في سهل ليتوم الى اقوى امبراطورية وبعد التوسعات الهائلة التي شهدتها خلال الحقبة الجمهورية رغم مانتج عنها من اثراء الموارد روما, لكنها عادة سلبا على الوضع الداخلي خاصة في القرن الاخير من حياة الجمهورية لم يعد ساسة الرومان قادرين على حكم هذا الاطار الجغرافي مما ادى الى سقوط الحكم في سوء الادارة . نتج عن هذا الوضع ظهور العديد من الشخصيات التي كان لها تاثير كبير على الاوضاع العامة في روما وادت في النهاية الى الانهيار النظام الجمهوري من بين ابرز الشخصيات في ذلك الوقت نذكر ; جايوس يوليوس قيصر وهو شخصية رومانية صنعت تاريخا اخر من خلال هذا البحث سنحاول فهم جميع الجوانب هذه الشخصية مع التاكيد على دوره السياسي كلمات مفتاحية -الحضارة الرومانية -العالم القديم - الحقبة الجمهورية ABSTRACT The Roman civilization is considered as one of the most important civilizations of the ancient world. It was able to impose its control over the Mediterranean Basin, especially after the fall of Carthage. It moved from a city in the plain of Latium to the most powerful empire after the massive expansions it witnessed during the Republican era, with all the enrichment of Rome’s resources that was caused by these expansions ; It had a negative impact on the internal situation, especially in the last century of the Republic's life, as Roman politicians were no longer able to rule this geographical framework, which led to the fall of the governing into mismanagement.This crisis situation resulted the emergence of many figures who had a great influence the thing that led at the end to the collapse of republican system.Among the most prominent figures that time, we mention Gaius the Julius Caesar, a Roman figure who made another history. Through this research, we will try to understand all aspects of this character, emphasizing his political role. Mots-clés: civilisation romaine - le monde antique-l'ère républicaine